Training Bahasa Inggris Dasar Peramu Wisata Untuk Forum Muda Berkarya (FMB) Desa Wisata Hijau Bilebante Kabupaten Lombok Tengah - Kamarudin Kamarudin; Tawali Tawali; Fathurrahman Imran (LPPM Universitas Pendidikan Mandalika (UNDIKMA), 2021)
This community service aims to improve knowledge, basic English skill for teenagers especially English for tour guide both theoretically and practically. This program involved the teenagers of Working Youth Forum (FMB) Bilebante Green Tourism Village, Central Lombok Regency. The presenters of this program were the English lecturers of UNDIKMA who are still active. The program took place in Bilebante Green Tourism Village, Central Lombok Regency. The method implemented planning, acting, and observing in which through giving the material presentation focusing on some materials such as; English for tourism, modal auxiliaries, eight parts of speech, and mini conversation practice realizing the materials given. The result of this community service revealed that the respondents were very enthusiastic and interest to participate actively within the process of the program given start from the first till the end. The capability of the respondents was also increase regarding on how to use English language expression for tour guide, vocabulary items, and become more confident. They expected the same program may be re-conducted or proceeded in another time since it has positive effect toward presentation, and their communicative English language skill.